Conceptualization and Measurement of Consumer Based Brand Equity for Airlines - Singh, Balgopal (Indian Journal of Marketing, 2018)
The study aimed at conceptualizing and measuring consumer based brand equity in the airline industry. This was achieved by focusing on the key dimensions of consumer based brand equity such as brand awareness, brand image, perceived service quality, and brand loyalty. The study proposed and tested a model of airline brand equity using a sample of 646 domestic air passengers. The research model was constructed on the recommendations of previous studies. To measure the dimensions of consumer based brand equity, a 13 item scale was constructed and validated using EFA and CFA. The scale exhibited convergent and discriminant validity. Measurement invariance test was conducted to examine the proposed brand equity dimensions as an indicator of the same latent variable for different airlines companies. Findings of the invariance test confirmed the equivalence of factorial measure across different airline brands. After the study, the model was validated through secondorder factor analysis. The research findings supported the four - dimensional model of consumer based brand equity in the airline industry. All the dimensions were confirmed to be related constructs and accounted for airline brand equity. The explanatory power of the dimensions of consumer based brand equity was calculated by examining the path coefficient of higher order construct. It was found that perceived service quality was the most reliable indicator and brand awareness the least. Finally, an ABE index was calculated for different airline brands based upon the weight of each dimension and mean value of constructs for different airline brands.